5‐Amido‐ and 5‐Amino‐Substituted Epoxyisoindolo[2, 1‐a]tetrahydroquinolines and 10‐Carboxylic Acids: Their Synthesis and Reactivity. (2nd April 2013) - Zaytsev, Vladimir P.; Zubkov, Fedor I.; Toze, Flavien A. A.; Orlova, Daria N.; Eliseeva, Maria N.; Grudinin, Dmitry G.; Nikitina, Eugeniya V.; Varlamov, Alexey V.
Abstract : The interactions between 4‐R‐substituted 2‐furyl‐1, 2, 3, 4‐tetrahydroquinolines (synthesized by the Povarov reaction) and a number of alkenes have been investigated. Maleic, dibromomaleic, dichloromaleic, and citraconic anhydrides, as well as acryloyl, methacryloyl, crotonyl, and cynnamoyl chlorides were used as alkene components. It was shown that the initial N ‐acylation of the tetrahydroquinolines was followed by a spontaneous [4+2]‐cycloaddition of an N ‐acryloyl substituent to the furan ring. It was established that the intramolecular Diels–Alder reaction of furans is reversible, occurs stereoselectively as exo ‐addition, and led to target epoxyisoindolo[2, 1‐ a ]tetrahydroquinolines with moderate yields. Oxidation and aromatization of the synthesized products were carried out. Abstract :